Drying behavior of steel-ladle lining refractory castables under continuous heating rate. Issue 1 (1st January 2022) - Cunha, T.M.; Moreira, M.H.; Santos, M.F.; Luz, A.P.; Pandolfelli, V.C.
Abstract: The current trend to replace shaped refractories for monolithics is related to various technical aspects, i.e., lack of joints, easier installation and free format. However, the main drawback of these non-shaped products is their longer first heat-up demand, otherwise mechanical failures or even explosive spalling may take place due to steam pressurization within the well packed consolidated structure. As a consequence, over-conservative drying schedules are commonly used in industrial equipment lined with such ceramics, which increase the energy consumption and the production down-time. Based on this scenario and considering the recent advances in numerical simulations, this article discusses the implications of applying different heating rates during the drying of a refractory castable lining of a steel ladle. Additionally, a novel methodology based on the correlation of the maximum vapor pressure and the mechanical strength of the ceramic material was also proposed. Using some of the castable properties measured as a function of temperature, simulation results pointed out that higher vapor pressures and a displacement of the maximum pressure peak are attained by applying high heating rates and thicker linings. This behavior is associated with the water migration to the inner regions of the refractory structure. It was observed that these conditions displace the maximum resistance ratio position towards the hot face, where most common spallings are observed. The work also emphasizes the importance of carrying out accurate measurements of physical properties as a function of the temperature, otherwise the outcome can be far from the reality of the working conditions.